Meningkatkan Keberanian Siswa melalui Strategi Pembelajaran Inkuiri pada Mata Pelajaran Akidah Akhlak - Arlina Arlina; Siti Rahmi Batubara; Zaidan Zega; Nurtika Syahputri; Cahaya Maharani Sitompul; Shofwan Agil Muwazif (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
To increase students' courage through inquiry learning strategies in the subject of moral ethics. This study aims to develop students' thinking skills so that they are able to encourage students' courage in expressing opinions or other matters related to the teaching and learning process which are oriented towards learning outcomes and learning processes. The research method used in this research is descriptive literature research, in which the researcher wants to describe the research carried out using literature in a more specific, transparent and in-depth manner. The results of this study, the researcher describes data related to the results of the literature regarding inquiry strategies, factors that influence the level of student courage, teacher strategies in increasing student courage and how to increase student courage through inquiry learning in the subject of moral ethics.